Validation of Scales for Researching Stakeholders’ Attitudes Toward Domestic Violence in China - Wretman, Christopher J. (Violence against women, 2025)
Domestic violence (DV) is a significant concern within China. Currently, there are few standardized measurement tools to gauge Chinese stakeholders’ perceptions and beliefs concerning DV. This research sought to validate tools to be used with such stakeholders. Factor analyses were utilized on cross-sectional, survey data from a purposive sample of 683 Chinese DV professionals working in four institutions in Guangdong. Analyses developed three scales for measuring DV Definitions, DV Attitudes, and DV Policing. The development of these scales is beneficial to advance the already growing research related to DV in China in ways that are relevant to the Chinese context.